Environmentally Friendly Lithium-Terephthalate/Polylactic Acid Composite Filament Formulation for Lithium-Ion Battery 3D-Printing via Fused Deposition Modeling. (19th March 2021) - Maurel, Alexis; Russo, Roberto; Grugeon, Sylvie; Panier, Stéphane; Dupont, Loic
Abstract : In this paper, the development of an environmentally-friendly lithium-terephtalate/polylactic acid (Li2 TP/PLA) composite filament, for its use, once 3D-printed via Fused Deposition Modeling (FDM), as negative electrode of a lithium-ion battery is reported. Solvent-free formulation of the 3D-printable filament is achieved through the direct introduction of synthesized Li2 TP particles and PLA polymer powder within an extruder. Printability is improved through the incorporation of poly(ethylene glycol) dimethyl ether average Mn ∼500 (PEGDME500) as plasticizer, while electrical performances are enhanced through the introduction of carbon black (CB). Thermal, electrical, morphological, electrochemical and printability characteristics are discussed thoroughly. By taking advantage of the 3D-printing slicer software capabilities, an innovative route is proposed to improve the liquid electrolyte impregnation within the 3D-printed electrodes.